Developing a Google Earth-Based Method to Measure Sight Distance for U-Turns at Unsignalized Intersections on Multilane Divided Highways. Issue 1 (January 2022) - Quan, Li; Zhang, Beijia; Zhou, Huaguo; Liu, Pan
The median U-turn is one of the most popular access management techniques implemented by state transportation agencies. Sight distance (SD) is among the key elements for the safe operation of median U-turns. The traditional method of measuring SD is using sight rods in the field, which is inconvenient and unsafe; thus, it is important to develop a convenient and safer method to measure SD for U-turn movement. The objective of this study is to develop a safe and cost-effective method to measure SD for U-turn vehicles, without going into the field, using existing tools in Google Earth and a perspective grid method that can be generated by Kinovea software. The method can be used in two different road geometric conditions: (i) a straight segment with crest curves; (ii) a roadway with a combination of crest curves and horizontal curves. For Condition (i), an empirical equation was developed to estimate SD as a function of distance and elevation along the sight line measured using Google Earth. For Condition (ii), a perspective grid was first applied using Google Earth ground-level view; then the number of broken lines and gaps in each perspective grid cell was used to measure the SD. All inputs can be collected using Google Earth. Field measurements of SD for U-turns at 10 selected locations were conducted to verify the validity of the method. The results show that the differences between the model estimates and field measurements are all less than 10%.